Resisting subjugation: law and power amongst the Santal of India and Bangladesh, 2002-2004 - Shariff, Fauzia (UK Data Service, 2006)
The study uses mixed methods and focuses on the Santal adivasi (tribal people) in Jharkhand, India and Rajshahi, Bangladesh. Anthropological and sociological data collection methods were used to collect material in four villages, three courts of law and from academics and activists. The focus of the data collection was to find evidence of how disempowered tribal people were able or not able to use the law to their advantage. A broad definition of law was used which acknowledged that the subjects of the research lived by a plurality of laws (state law, their customary law and norms directing their relationships in the village and the home). The main focus of the study was to understand how individuals related to these different laws and legal orders and the factors that affected their empowerment or disempowerment through law. The collection has been enhanced by the conversion of the qualitative data from Atlas.ti software to RTF format. The Atlas.ti files underwent checks and editing before conversion and are also available for dissemination; enabling data manipulation and querying within the database.